Catalytic cascade reactions - Xu, Peng-Fei, 1964-; Wang, Wei (Associate professor of chemistry) (Wiley, 2014)
"The development of catalytic versions of cascade reactions has become one of the most active and burgeoning reaction areas in organic synthesis. Covering both organocatalysis and transition-metal catalysis for these reactions, Catalytic Cascade Reactions illustrates the versatility and application of cascade reactions for synthesizing valuable compounds, such as drugs and natural products. Highlighting catalytic versus non-catalytic reactions, an important shift in academic and industry practice, the text brings chemists and the organic synthesis community up to speed on the many recent advances in the field"--